Preschool children with persistent asthmatic symptoms - Vogelberg C (Dove Medical Press, 2019)
Christian Vogelberg Department of Pediatric Pulmonology and Allergy, University Hospital Carl Gustav Carus, Technical University of Dresden, Dresden, Germany Abstract: Asthma is the most common chronic airway disease in children, with more than half the reported cases of persistent asthma starting in children below the age of 3 years. Asthma diagnosis in preschool children has proven to be challenging due to the heterogeneity of the disease, the continuing development of the immune system in such a young population, and lack of diagnostic options such as lung function measurement. Early diagnosis and treatment of asthmatic symptoms will improve patients’ quality of life and help reduce disease morbidity. However, validated treatment options are scarce due to paucity of data and lack of conclusive studies in such a young patient population. Adjusting study design and endpoints to capture more reliable data with minimal risk of harm to patients is necessary. This thematic series review outlines the current position on preschool asthma, consolidates the current understanding of risk factors and diagnostic hurdles, and emphasizes the importance of early detection and management to help improve patients’ quality of life, both present and future. Particular focus was given to anticholinergics and their emerging role in the treatment and control of asthma in pediatric patients. Keywords: preschool children, asthmatic symptoms, tiotropium, anticholinergic